Controversies in Mediastinal Staging for Nonsmall Cell Lung Cancer - Ashok, Apurva; Jiwnani, Sabita S.; Karimundackal, George; Bhaskar, Maheema; Shetty, Nitin S.; Tiwari, Virendra Kumar; Niyogi, Devayani M.; Pramesh, C. S. (Indian Journal of Medical and Paediatric Oncology, 2021)
Mediastinal lymph nodal involvement in nonsmall cell lung cancer plays a crucial role in deciding treatment strategy. Survival falls markedly with increasing involvement of mediastinal nodal stations. Hence, accurate staging of the mediastinum with lowest morbidity is of utmost importance. A wide array of invasive and noninvasive modalities that complement each other in assessing the nodes are available at our disposal. Guidelines recommend noninvasive imaging as the initial step in the staging algorithm for all tumors, followed by invasive staging. No single modality has proven to be the ideal method to stage the mediastinum when used alone. In the present decade, minimally invasive endobronchial ultrasound (EBUS) has challenged the position of surgical mediastinoscopy, which has been the gold standard, historically. However, a negative EBUS needs to be confirmed by surgical mediastinoscopy. Video-assisted mediastinoscopic lymphadenectomy has also come to the forefront in last two decades and has shown exceptional results, when performed in experienced centers. This review details the various modalities of mediastinal staging and the controversies surrounding the optimal method of staging, restaging after neoadjuvant therapy, and the most cost-effective strategy.
Keywords: mediastinal staging; endobronchial ultrasound; mediastinoscopy; VAMLA; nonsmall cell lung cancer